Does neighborhood green infrastructure (NGI) affect residents’ self-perceived health? - Mansor, Mazlina; Zakariya, Khalilah; Harun, Nor Zalina (American Scientific Publishers, 2017)
Research has shown that physical inactivity is prevalent among urban residents. It is due to sedentary living and spending a little time on outdoor recreational activities. This study implies that nearby parks, green spaces or even activities on neighborhood streets can increase participation in the outdoors, thus improve health. The aim of the study was to investigate whether neighborhood green infrastructure (NGI) relates to urban residents’ self-perceive health. The findings were derived from 650 self-administered survey questionnaires, which were distributed to residents in Bandar Tun Razak. Findings suggest that the NGI encourages physical and recreational activities and satisfaction to health. Therefore, a connected NGI in towns and cities will increase the pursuit of a healthy lifestyle and promotes health equity. The unbroken sequential journey from home via tree-line streets and sidewalks with neighborhood open spaces and recreational park allows users to experience nature in the built environment. The health effects that are experienced by the urban residents will provide a basic framework to promote health by design. This finding can be translated into policy on health promotion in Malaysia through landscape design and planning of urban green spaces. Keywords: Neighborhood green infrastructure (NGI), Urban residents, Sequential experience, Health.